Intra-adrenal interactions in fish: Catecholamine stimulated cortisol release in sea bass (Dicentrarchus labrax L.) - Rotllant, J. (2014)
The effect of the catecholamines, adrenaline and noradrenaline, on sea bass (Dicentrarchus labrax) and sea bream (Sparus auratus) interrenal cortisol production was studied in vitro using a dynamic superfusion system technique. Increasing concentrations of catecholamines (10−6, 10−8 and 10−10 M) stimulated cortisol production in a dose-dependent manner, in sea bass only. The increase in cortisol production stimulated by adrenaline (10−6 M) and noradrenaline (10−6 M) was inhibited by sotalol (2×10−5 M), but not by prazosin suggesting that catecholamines stimulate cortisol release through the β-receptor subtype. To evaluate catecholamine-induced signal transduction in head kidney cells, measurements of cAMP production and [H3]myo-inositol incorporation were determined in head kidney cell suspensions. Adrenaline and noradrenaline (10−6 M) increased cAMP production, but had no effect on total inositol phosphate accumulation. These results indicate that catecholamines released from the chromaffin cells within the interrenal tissue may act as a paracrine factor to stimulate interrenal steroidogenesis in the sea bass.